1,2-Bis[5-(2,2′-dicyanovinyl)-2-n-pentyl-3-thienyl]-3,3,4,4,5,5-hexafluorocyclopent-1-ene: a new photochromic diarylethene compound - Li, Min (International Union of Crystallography, 2008)
The title compound, C(31)H(26)F(6)N(4)S(2), is a new photochromic dithienylethene with dicyanovinyl subsitituents. In the crystal structure, the molecule adopts a photoactive antiparallel conformation, with two n-pentyl groups located on opposite sides of the cyclopentene ring. The cyclopentene ring assumes an envelope conformation. The distance between the two reactive C atoms on the thiophene rings is 3.834 (7) Å. One of the n-pentyl groups is disordered over two positions; the site occupancy factors are ca 0.7 and 0.3.